2019
DOI: 10.1177/1179556519835833
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and Validity of the Japanese Version of the Physical Activity Questionnaire for Older Children

Abstract: Objectives:This study aimed to examine the reliability and validity of the Japanese version of the Physical Activity Questionnaire for Older Children (PAQ-C) in Japanese children aged 9 to 12 years.Methods:A total of 210 children aged between 9 and 12 years participated. Internal consistency and test-retest reliability were evaluated using Cronbach alpha coefficient and intraclass correlation coefficient (ICC), respectively. Validity was evaluated using athletic competence (AC), self-efficacy (SE), body mass i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
21
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(31 citation statements)
references
References 40 publications
6
21
0
4
Order By: Relevance
“…First, Cronbach’s α, performed to check PAQ-C internal consistency, was found to be 0.78 for the 7th grade, a value that was similar to previous PAQ-C adaptations in several countries [ 37 , 38 , 39 , 46 , 47 ]. The estimates for the 4th grade and the total sample were lower; nevertheless, taking into account that a value of Cronbach’s α higher than 0.70 suggests a reliable questionnaire [ 43 ], our results suggest satisfactory internal consistency of the PAQ-C in Greek children.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…First, Cronbach’s α, performed to check PAQ-C internal consistency, was found to be 0.78 for the 7th grade, a value that was similar to previous PAQ-C adaptations in several countries [ 37 , 38 , 39 , 46 , 47 ]. The estimates for the 4th grade and the total sample were lower; nevertheless, taking into account that a value of Cronbach’s α higher than 0.70 suggests a reliable questionnaire [ 43 ], our results suggest satisfactory internal consistency of the PAQ-C in Greek children.…”
Section: Discussionsupporting
confidence: 74%
“…The estimates for the 4th grade and the total sample were lower; nevertheless, taking into account that a value of Cronbach’s α higher than 0.70 suggests a reliable questionnaire [ 43 ], our results suggest satisfactory internal consistency of the PAQ-C in Greek children. As far as its test–retest reliability is concerned, research evidence supports the stability of the PAQ-C over time, since it has been found to present moderate (ICC = 0.73 [ 26 ]; 0.75 [ 48 ]), good (ICC = 0.82 [ 38 ]; 0.83 [ 39 ]) and excellent (ICC = 0.90) [ 49 ]; 0.96 [ 46 ]) test–retest reliability. The variability of the aforesaid ICCs can be attributed to the wide range of the time intervals used for readministering the PAQ-C in the above studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This led to our modifying the spare-time activities checklist as we mentioned in the Methods section to better reflect the structure of school time in Czechia and children’s overall movement behaviour during school days. Such changes and replacements to such questionnaires are not isolated—similar item modifications, removals, or additions were made in other language versions or modifications of the PAQ-C as well [ 17 19 , 21 , 22 , 24 , 25 , 44 , 45 ]. Data collection was practical in that completion of the questionnaire took 10–35 minutes, which is acceptable.…”
Section: Discussionmentioning
confidence: 99%
“…PA was assessed using the Japanese version of PAQ-C which had acceptable reliability and validity (In this study: Cronbach’s alpha = .81) (Isa et al, 2019). The PAQ-C is a self-reported seven-day recall questionnaire for children aged 8–14 years (Crocker et al, 1997; Kowalski et al, 1997).…”
Section: Methodsmentioning
confidence: 99%